2012
DOI: 10.12693/aphyspola.121.502
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Glass Coatings Synthesized by Pulsed Laser Deposition Technique

Abstract: Surface modification of medical implants is often required to improve their biocompatibility or, through bioactive properties of the surface material, facilitate its intergrowth with the living tissue. Bioactive-glass coatings can serve that purpose for the bone implants. We report a successful preparation of silicate-phosphate bioactive-glass coating on titanium substrate using the pulsed laser deposition method and present the coating characterization in terms of bonding configuration and chemical activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…The feature near 814 cm À1 is attributed to the CC 4 symmetric stretching of the PMMA molecules. 38 38,39 This spectral evidence confirms the formation of the PMMA-Bioglass composites. The spectral intensity of phosphate and Q 4 is slightly higher in the ethanol-water prepared scaffold as indicated by the vertical lines.…”
Section: Phase Confirmation Using Micro Raman Analysissupporting
confidence: 73%
See 1 more Smart Citation
“…The feature near 814 cm À1 is attributed to the CC 4 symmetric stretching of the PMMA molecules. 38 38,39 This spectral evidence confirms the formation of the PMMA-Bioglass composites. The spectral intensity of phosphate and Q 4 is slightly higher in the ethanol-water prepared scaffold as indicated by the vertical lines.…”
Section: Phase Confirmation Using Micro Raman Analysissupporting
confidence: 73%
“…) and Q 4 (Si-O-Si = 1601) components respectively. 39 In general, the high abundance of the Q 2 component represents a higher bioactivity in the bioactive glasses. Furthermore, the peaks present at 954 and 974 cm À1 are due to the P-O symmetric vibrations (PO 4 3À ) and P-O-P stretching vibrations of the phosphate molecules present in the glass network.…”
Section: Phase Confirmation Using Micro Raman Analysismentioning
confidence: 99%
“…The band in this spectral region is also characteristic for the asymmetric stretching of Q 4 Si units [45,46]. The broadening of the 1073 cm −1 band suggests the presence of these entities in the structure of A2_gel glass.…”
Section: Raman Spectroscopymentioning
confidence: 81%
“…Raman spectrum shows the band at 1034-1051 cm −1 , which corresponds to asymmetric stretching of bridging oxygen in Q 1 , Q 2 , Q 3 and Q 4 Si units [44,46]. Furthermore, two bands at 958-972 cm −1 and 1000-1019 cm −1 indicate the presence of Q 0 and Q 1 P entities, respectively [28,44,47].…”
Section: Raman Spectroscopymentioning
confidence: 98%
“…Likewise, Si‐O‐Si bending vibration was observed in the range of 833 cm −1 (Aguiar, Serra, Gonzalez, & Leon, 2009). The band at 938 cm −1 in 800‐3h structure is dominated with Q 2 metasilicate chains (Si 2 O 6 4− ), Kwiatkowska, Suchanek, and Rajchel (2012) reported that abundance of Q 2 vibrations in bioactive materials has the characteristic nature of high bioactivity. In all the bioactive materials, around 960 to 970 cm −1 peaks designate the P‐O symmetric vibrational modes (Notingher et al, 2003).…”
Section: Resultsmentioning
confidence: 99%